Is postablation whole‐body 131I scintigraphy still necessary in intermediate‐risk papillary thyroid cancer patients with pre‐ablation stimulated thyroglobulin <1 ng/mL?. (15th August 2016) - Liu, Bin; Chen, Yu; Jiang, Lisha; He, Ying; Huang, Rui; Kuang, Anren
Summary: Objective: Postablation whole‐body scintigraphy, which is performed 5–7 days after administration of ablation activity of radioactive iodine‐131 ( 131 I) in patients with thyroid cancer, is considered a routine procedure for remnant ablation and a useful tool for disease staging. However, the relationship of pre‐ablation stimulated thyroglobulin (s‐Tg) levels with postablation scintigraphic findings has not been evaluated. The current study was designed to determine the diagnostic value of postablation 131 I scintigraphy during initial staging and risk stratification in intermediate‐risk papillary thyroid cancer (PTC) patients with pre‐ablation s‐Tg < 1 ng/ml at the time of ablation. Design: From January 2013 to July 2015, consecutive PTC patients at intermediate‐risk of recurrence according to American Thyroid Association criteria were prospectively recruited. Patients had to have pre‐ablation s‐Tg < 1 ng/ml in the absence of anti‐Tg antibody at the time of ablation. Systematic pre‐ablation neck ultrasonography was performed for each patient. Postablation whole‐body planar scintigraphy was obtained 5 days after administration of ablation activity of 131 I. Single photon emission computed tomography/low‐dose computed tomography was added for patients whose planar findings were inconclusive. Results: Among 756 patients ablated, 240 (31·7%) patients were eligible for the analysis. Pre‐ablation neck ultrasonography revealed lymph node metastases in eight of the 240 patients. Postablation scintigraphy showed ectopic neck uptake corresponding to the lymph nodes seen by ultrasonography in four patients and revealed neck lymph node metastases in another two patients whose ultrasonography findings were negative. None of the 240 patients showed distant metastasis on postablation scintigraphy. Neither staging nor initial risk stratification was altered by postablation scintigraphy in the included patients with pre‐ablation s‐Tg < 1 ng/ml. Conclusions: As postablation whole‐body scintigraphy played a minimal role in improving staging or initial risk stratification in intermediate‐risk PTC patients with pre‐ablation s‐Tg < 1 ng/ml, we propose that postablation scintigraphy may be omitted in this group of patients. Multi‐institutional larger studies are necessary to draw definitive conclusions.